Aplikasi Pendidikan Online “Ruang Guru” Sebagai Peningkatan Minat Belajar Generasi Milenial Dalam Pembelajaran Pendidikan Pancasila Dan Kewarganegaraan - Manuhuruapon, Jenika; Toganti, Nadia; Biringan, Julien (CV. Kurnia Grup, 2024)
This article discusses the application of Ruang Guru, an online education platform, in enhancing the learning interest of millennials. Education is vital for human development, as it provides valuable insights and knowledge. Every individual deserves access to quality education, regardless of their location, as education can transform mindsets positively. One innovative approach to education is using smartphones or gadgets as educational tools, exemplified by the Ruang Guru application. Ruang Guru is a digital-based application accessible anytime and anywhere, offering an easy-to-use interface that aids in solving learning challenges. It provides a comprehensive learning management system for students and teachers to manage classroom activities virtually. Additionally, it features thousands of practice questions aligned with the Indonesian curriculum.